2021
DOI: 10.1101/2021.03.19.21253963
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of information about COVID-19 vaccine effectiveness and side effects on behavioural intentions: two online experiments

Abstract: The success of mass COVID-19 vaccination campaigns rests on widespread uptake. However, although vaccinations provide good protection, they do not offer full immunity and while they likely reduce transmission of the virus to others, the extent of this remains uncertain. This produces a dilemma for communicators who wish to be transparent about benefits and harms and encourage continued caution in vaccinated individuals but not undermine confidence in an important public health measure. In two large pre-registe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…As COVID‐19 vaccines continue to be developed, evaluated, and improved, honest and up‐to‐date information about COVID‐19 vaccination effectiveness, side effects, and safety needs to be made available to the public (Karlsson et al, 2021). However, providing information alone does not change vaccination uptake intention (Kerr et al, 2021). Building trust is critical in increasing engagement with vaccination programmes; government representatives and authority figures need to be mindful of this, particularly in marginalized groups, and need to communicate information about vaccines clearly and honestly (Enria et al, 2021; Fancourt et al, 2020; OECD, 2021; Parsons & Wiggins, 2020; Paul et al, 2021; Reid & Mabhala, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As COVID‐19 vaccines continue to be developed, evaluated, and improved, honest and up‐to‐date information about COVID‐19 vaccination effectiveness, side effects, and safety needs to be made available to the public (Karlsson et al, 2021). However, providing information alone does not change vaccination uptake intention (Kerr et al, 2021). Building trust is critical in increasing engagement with vaccination programmes; government representatives and authority figures need to be mindful of this, particularly in marginalized groups, and need to communicate information about vaccines clearly and honestly (Enria et al, 2021; Fancourt et al, 2020; OECD, 2021; Parsons & Wiggins, 2020; Paul et al, 2021; Reid & Mabhala, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…One study found that messages emphasizing "personal health risks and collective health consequences of not vaccinating significantly increase Americans' intentions to vaccinate" (Motta et al 2021, 1). Other studies, however, do not report a relationship between providing detailed information on the efficacy or safety of COVID-19 vaccines and the willingness to get vaccinated (Duquette 2020;Kerr et al 2021). Transparency about the pros and cons of the vaccine is necessary but not sufficient to convince people to get vaccinated (Petersen et al 2021).…”
Section: Overcoming Vaccine Hesitancymentioning
confidence: 99%
“…Two survey experiments conducted in the United Kingdom and the United States found that providing information about prosocial benefits and herd immunity effectively increased participants' willingness to get vaccinated against COVID-19 (31), whereas two other survey experiments from France and the United Kingdom reported null effects (15,21). Four United States-based studies found that messages emphasizing the effectiveness and low risk of side effects associated with the COVID-19 vaccines significantly increased willingness to get vaccinated (20,31,32), while a similar United Kingdom-based study did not find any such effects (33). A survey experiment conducted in the Netherlands found that debunking specific vaccination myths, such as "vaccination can cause autism," resulted in more favorable attitudes toward COVID-19 vaccines (34).…”
Section: Introductionmentioning
confidence: 99%